A novel approach to classify risk in dengue hemorrhagic fever (DHF) using bioelectrical impedance analysis (BIA) - Ibrahim, F.; Taib, M.N.; Wan Abas, W.A.B.; Guan, C.C.; Sulaiman, S. (2005)
This paper introduces a novel approach to classify the risk in dengue hemorrhagic fever (DHF) patients using the bioelectrical impedance analysis (BIA) technique. This in vivo technique involves the application of a small average constant current of less than 1 mA at a single frequency of 50 kHz through the human body, and measurement of the body's bioelectrical resistance (R), phase angle (Î±), body capacitance (BC) and capacitive reactance (Xc) via four surface electrodes. BIA measurements have been conducted on 184 (97 males and 87 females) serological confirmed dengue patients during their hospitalization in University Kebangsaan Malaysia Hospital, Malaysia. The patients included in the study were DHF I-IV according to World Health Organization criteria. Univariate analysis of variance is used for assessing the relationship between gender and group with the bioelectrical tissue conductivity (BETC) parameters. Experimental findings show that BETC, as reflected by reactance, is the key determinant indicator for classifying risk category in the DHF patients. Hence, this novel approach of the BIA technique can provide a rapid, noninvasive, and promising method for classifying and evaluating the risk of the DHF patients.